2023
DOI: 10.1111/dom.15201
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of canagliflozin and dapagliflozin for treatment of patients with chronic kidney disease and type 2 diabetes

Abstract: AimTo examine the cost‐effectiveness of adding canagliflozin or dapagliflozin to standard of care (SoC) versus SoC alone in patients with chronic kidney disease (CKD) and type 2 diabetes (T2D).Materials and MethodsWe used a Markov microsimulation model to assess the cost‐effectiveness of canagliflozin plus SoC (canagliflozin + SoC), dapagliflozin plus SoC (dapagliflozin + SoC) and SoC alone. Analyses were conducted from a healthcare system perspective. Costs were measured in 2021 Canadian dollars (C$), and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Similarly, another study illustrated the cost-effectiveness of dapagliflozin for patients with stage 3b CKD in Japan (Kodera et al, 2022). A very recent analysis showed that the use of canagliflozin or dapagliflozin, added to the standard of care (SoC) in patients with CKD and DM, was more cost-effective than SoC only (Nguyen et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…Similarly, another study illustrated the cost-effectiveness of dapagliflozin for patients with stage 3b CKD in Japan (Kodera et al, 2022). A very recent analysis showed that the use of canagliflozin or dapagliflozin, added to the standard of care (SoC) in patients with CKD and DM, was more cost-effective than SoC only (Nguyen et al, 2023).…”
Section: Figurementioning
confidence: 99%
“… 5 Nationally, patients with diabetes pay approximately $150 to $500 per year for antidiabetic medications. 6 Most employer-sponsored plans, whether or not they have a high deductible for medical services, apply co-payments to prescriptions. 7 A less common plan type, 8 high-deductible health plans with health savings accounts, subjects almost all medications to the deductible.…”
Section: Introductionmentioning
confidence: 99%